Disinformation narratives: Impact, exposure and role of ideology - Puertas-Graell, David; Suau-Martinez, Jaume (Estudios sobre el Mensaje Periodístico, 2025)
Misleading information stands as a central concern in terms of societal, political, and journalistic concerns. The strategic and deliberate dissemination of falsehoods contributes to the construction of narratives capable of blurring the lines between truth and plausibility. These narratives are understood as forms of discursive rhetoric, stories laden with significant meaning, functioning to shape citizens’ understanding of events. This research examines the impact, exposure, and ideological component that accompanies misinformation. A series of misinformation narratives have been identified, based on material previously classified as misinformation by Spanish fact-checkers (Newtral, Maldita, and Verificat), relying on the fact-checks published on their websites. Subsequently, a database was built that categorizes the fact-checks according to keywords and topics addressed. In total, 163 fact-checks were collected. Finally, has been conducted a survey (N=1,003) of Spanish residents aged 18 to 74 with a margin of error of +/- 3.4% at a 95% confidence level, where p=q=0.5. The findings underscore the relevance of prior exposure to misinformation content in attributing a certain degree of credibility to it. Additionally, both the topic and framing employed to present the information establish differences in exposure as well as the acceptance or impact of the message.